ANALISIS PENINGKATAN KUALITAS PELAYANAN INTERNAL DIBAGIAN UMUM SETDAKAB ACEH SELATAN - Listia, Mera (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2022)
The purpose of this study was to determine the improvement of service quality in the general section of the Aceh Selatan Secretariat whether it has good service for employees. The research method used is the index method through a quantitative approach. Data collection techniques used questionnaires. The research instrument is as stated in the canon of the minister for the utilization of state apparatus and the renewal of functionaries No. 14 of 2017 regarding the recording instructor of the Community Satisfaction review. From the research perspective,it can be determined that the Community Satisfaction Index in the General Section of the Regional Secretariat of South Aceh Regency is running very well. This activity can be seen in 9 (nine) instructions according to (Permenpan-RB) Number 14 of 2017 through the average superiority of repairs domiciled according to very good and good categories. The service that has the highest value element is the System, Mechanism,and procedure which stores the IKM change value of 88.85 and exists according to a very good rank.